Development of multi-component counseling program for enhancing resilience among Thai caregivers of older persons with dementia - Thidajit Maneewat; Somrat Lertmaharit; Sookjaroen Tangwongchai; Phenphop Phansuea (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study was to develop a multi-component counseling program and examine the short-term effects of an 8-session program. Design/methodology/approach - This present study was a research and development of a multi-component counseling program for enhancing resilience. The concept of resilience was reviewed based on a synthesis of existing research, together with an exploration of qualitative data derived from an interview with ten caregivers of older persons with dementia. Six domains of resilience were identified: physical, relationships, emotional, moral, cognitive and spiritual; which were then used to develop the eight-week program. The program was examined by a panel of three experts for content validity, which yielded an index of 0.87. The program was then tried out with 60 caregivers recruited and assigned 30 caregivers in the intervention and control group. The Caregiver's Resilience Scale (CRS) was used by trained nurses to evaluate the program and data were analyzed using repeated measures ANOVA. Findings - The results indicated that the resilience scores of the participants in the intervention group were statistically significantly higher than those of the control group at one month after program participation and at the follow-up three months later (p < 0.05). Originality/value - It could be concluded that the program yielded support for the evidence-based practice of non-pharmacological intervention. The program would be suitable as a clinical practice guideline to provide help to caregivers of older persons with dementia at the outpatient setting.